Análisis de la eficiente aplicación de la legislación interna para los procedimientos de declaratoria de utilidad pública en el Gobierno Autónomo Descentralizado del cantón Riobamba - Teresa Alexandra, Sandoval Rosero (2023)
ABSTRACT In the present work, the application of the internal legislation in the procedures of declaration of public utility is analyzed through a doctrinal, legal and case study, in the Autonomous Decentralized Municipal Government of Riobamba. To achieve this objective, a qualitative methodology is applied to the theoretical and normative sources that address the unit of analysis, which are the declaration procedures of public utility that are carried out in the GAD Riobamba, with respect to which a characterization and assessment is made in regarding the application of current national and local regulations. To complement the results of the doctrinal and normative study, a survey was applied to ten experts linked to said processes, and 16 cases of declaration of public utility were analyzed where only in one of them an agreement was not reached with the owners, for which reason the others were paid the cadastral value of the property plus an additional 10% provided for in the law when there is an agreement. With the owner who did not reach an agreement, only the cadastral value was canceled. The main result is a characterization of the processes of declaration of public utility and the applied regulations, based on which it is concluded that although there was an agreement in most cases, paying the cadastral value and not the market value is unfair. for the affected owners, and that the disagreement that is unfairly penalized with the non-payment of an additional 10% of the cadastral value. Keywords: public utility, constitutional precedents, legislation, administrative procedure, administrative act.